Պետության ինքնիշխանության դրսևորման ձևերը Հայաստանի Հանրապետության սահմանադրական կարգավորումների արդիականացման շրջանակում - Աշոտ Խաչատրյան; Արամ Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В статье были затронуты проблемы исследования суверенитета конституционного закрепления и форм его проявления в контексте современного конституционного регулирования Республики Армения. The article discusses the issues of constitutional fixing of sovereignty and the observation of manifestation forms from the viewpoint of new Constitutional Regulations of the Republic of Armenia.
Keywords: Law